2002
DOI: 10.1046/j.1442-2042.2002.00442.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal metastasis from renal cell carcinoma: Significance of adrenalectomy

Abstract: Background: The present study examined adrenal metastasis resulting from renal cell carcinoma (RCC), with the aim of assessing the need for routine ipsilateral adrenalectomy during radical nephrectomy. Methods: Ipsilateral and contralateral adrenal metastases were investigated in 256 patients with RCC who had undergone radical nephrectomy from 1977 to 1996 at the Tohoku University School of Medicine.Results: Twelve of the 256 patients (4.7%) had adrenal metastasis. Ten of these 12 patients had progressed to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
1
10
0
2
Order By: Relevance
“…Disseminated cancer is the term used for metastases (known preoperatively) in the NSQIP data set and probably represents adrenal metastases in this study. A few single-center studies have investigated LA among patients with adrenal metastases, but these are limited in number [28][29][30][31][32]. Previous findings have shown that LA is equivalent to OA in terms of margin status, local recurrence, disease-free interval, and overall survival, providing a significantly shorter operative time, a shorter LOS, and fewer total complications [32].…”
Section: Discussionmentioning
confidence: 99%
“…Disseminated cancer is the term used for metastases (known preoperatively) in the NSQIP data set and probably represents adrenal metastases in this study. A few single-center studies have investigated LA among patients with adrenal metastases, but these are limited in number [28][29][30][31][32]. Previous findings have shown that LA is equivalent to OA in terms of margin status, local recurrence, disease-free interval, and overall survival, providing a significantly shorter operative time, a shorter LOS, and fewer total complications [32].…”
Section: Discussionmentioning
confidence: 99%
“…The most common primary malignancies to metastasize to the adrenal gland are lung, kidney, breast, or gastrointestinal carcinomas. Recently, the detection rate of clinically silent adrenal lesions has increased, due to the widespread use of abdominal imaging modalities [1,2]. Siemer et al [23] reported that adrenal metastases of primary renal cell carcinoma were found in 5.5% of patients and more often in patients with an advanced tumour stage.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of adrenal metastases found at autopsy is 8.6-27% of all malignancies [1,2]. Adrenalectomy and laparoscopic partial adrenalectomy are the standard treatment for adrenal masses [3][4][5] and provide effective management of adrenal metastases [6,7]; however, the risks involved in surgery, such as bleeding or inflammatory complications, are significant.…”
Section: Introductionmentioning
confidence: 99%
“…Die Operationstechnik hat sich heutzutage aufgrund der in der überwie-genden Mehrzahl der Fälle inzidentellen Tumordiagnose mit relativ kleinem Primärtumor dahingehend gewandelt, dass eine synchrone Adrenalektomie nur noch bei auffälligem Befund der Nebenniere in der präoperativen CT-Diagnostik, bei einem bereits bildgebend gesicherten T3-Tumor und bei Nachweis synchroner systemischer Metastasen durchgeführt wird [3]. Die genannten Konstellationen sind mit einem adrenalen Metastasierungsrisiko von bis zu 10% assoziiert, während bei dem typischen T1/2-Tumoren eine Nebennierenmetastase in maximal 2% nachweisbar ist ( [7,8,9,10,11]; . Tab.…”
Section: Radikale Tumornephrektomieunclassified
“…Obwohl heute als Standard empfohlen, wurden und werden organerhaltende Operationen bei Nierentumoren >T1b häufig nur bei ausgewählten Patienten mit einer funktionellen Einzelniere oder bei Patienten mit stark eingeschränkter Nierenfunktion unter imperativer Indikation durchgeführt. Weltweit werden Patienten mit lokal begrenzten Nierentumoren immer noch überproportional häufig radikal nephrektomiert [7,26]. In einer aktuellen retrospektiven Studie untersuchten Hellenthal et al [26] 59.944 Patienten, die in den Jahren 1988-2005 eine radikale Nephrektomie oder eine organerhaltende Operation bei NNZK erhalten hatten.…”
Section: Organerhaltende Nierentumorchirurgie Bei Tumoren ≥T1bunclassified